Administrator’s Role and Organizational Climate of Primary School in Nonthaburi Province. - Supasirithananon, Rinyapath; Tonwimonrat, Sakdipan (Saengtham College Journal, 2021)
The purposes of this research were to know 1) the administrator’s role of the Nonthaburi Primary Educational Schools 2) the organization climate of the Nonthaburi Primary Educational Schools and 3) the relationship between the administrator’s role and the organization climate of the Nonthaburi Primary Educational Schools. The sample were 76 schools under Nonthaburi Primary Education Service Area Office 1 and 2. The respondents from each school were the directors and teachers total of 152. The instrument was a questionnaire about the decision -making of administration and the school's effectiveness. The statistical used to analyze the data were frequency (f), percentage (%), arithmetic mean (x̅), standard deviation (S.D.) and Pearson’s product moment correlation coefficient. The finding of this research were as follows: 1.The administrator’s role of the Nonthaburi Primary Educational Schools, as a whole and an individual, were at a high level. 2.The organizational climate of the Nonthaburi Primary Educational Schools, as a whole and an individual, was at a high level. 3.There was a significant relationship between the administrator’s role and the organizational climate of the Nonthaburi Primary Educational Schools at .01 level.